Backward-looking sentence processing in typically disfluent versus stuttered speech: ERP evidence. Issue 5 (28th May 2019) - Maxfield, Nathan D.; Ferreira, Fernanda
ABSTRACT: The aim was to determine how backward-looking sentence processing is affected by typically disfluent versus stuttered speech. Two listener groups heard Garden Path (GP) and control sentences. GP sentences contained no disfluency, a silent pause, or a filled pause before the disambiguating verb. For one group, the sentence preambles additionally contained stuttering-like disfluencies. Comprehension accuracy, event-related potentials (ERPs) time-locked to disambiguating verbs, and perceptual speaker ratings, were compared between groups. The With Stuttering group perceived the speaker as less competent but had better comprehension accuracy for GP sentences. ERPs to disambiguating verbs in GP sentences included a P600 component, indexing backward-looking sentence processing, but only for the No Stuttering group. Other ERP components, elicited to GP sentences with silent/filled pauses, did not differ between groups. Results suggest that listeners abandon prior expectations when processing sentences containing stuttering-like disfluencies, possibly because they lack a speaker model defined by the presence of stuttering.